\begin{align}
ΣM_S=0
=&\cssId{Step1}{M_A - M_{mg} - M_{mpg}}\\[3px]
&\cssId{Step2}{F_A * x_{min1} - mg * x_{min2} - m_pg * x_{min3} =0}\\[3px]
&\cssId{Step3}{F_A = \frac{mg * x_{min2} + m_pg * x_{min3}}{x_min1}}\\[3px]
\end{align} (_{S} = suport)
(m = person's mass)
(m_{p} = planck's mass)

- In the first step we make the summation of momentums from point S (suport)
- In the second step we express every momentum as the product of the force (F
_{A}, mg, etc.) and the minimum distance, of these forces, from point S (x_{min1},x_{min2, etc.)} - In the third step we isolate F
_{A}to one side of the equation and everything else to the other side so that you can solve the equation